2022
DOI: 10.3390/ani12111356
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Selective Analysis of Boer Goat to Investigate the Dynamic Heredity Evolution under Different Stages

Abstract: Boer goats, as kemp in meat-type goats, are selected and bred from African indigenous goats under a long period of artificial selection. Their advantages in multiple economic traits, particularly their plump growth, have attracted worldwide attention. The current study displayed the genome-wide selection signature analyses of South African indigenous goat (AF), African Boer (BH), and Australian Boer (AS) to investigate the hereditary basis of artificial selection in different stages. Four methods (principal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The population structure analysis indicated a consistent clustering pattern based on PCA, NJ phylogenetic trees and admixture analyses. It has been noted that in the experimental samples, apart from the wild goat population, IBE, the other six domestic goat populations were clustered into four groups, which is generally in agreement with their economic traits [47].…”
Section: Population Structure and Linkage Disequilibriumsupporting
confidence: 62%
“…The population structure analysis indicated a consistent clustering pattern based on PCA, NJ phylogenetic trees and admixture analyses. It has been noted that in the experimental samples, apart from the wild goat population, IBE, the other six domestic goat populations were clustered into four groups, which is generally in agreement with their economic traits [47].…”
Section: Population Structure and Linkage Disequilibriumsupporting
confidence: 62%
“…As we are aware, the Boer goat is recognized globally as one of the finest meat goat breeds, originating from the Republic of South Africa (Yuan et al., 2022). Owing to its exceptional meat production performance, it has been introduced by numerous countries.…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphism (SNP), as the third-generation DNA molecular marker, has the advantages of dense distribution, low typing error, genetic stability and low cost. It is widely used in evolutionary research [ 3 , 4 , 5 , 6 , 7 , 8 ] and genetic relationship identification [ 9 , 10 , 11 , 12 , 13 , 14 ]. One study revealed the genetic diversity of the global goat population and highlighted the migratory routes after domestication based on a 50K SNP chip [ 15 ].…”
Section: Introductionmentioning
confidence: 99%